Coprodução para prevenção aos riscos climáticos: diagnóstico e perspectivas no município de Aracaju, Sergipe - Almeida, Maura Edite dos Santos (2024)
This paper aims to describe the role of coproduction in preventing climate risks at a local scale, presenting perspectives from a literature review in different countries and a documentary analysis of a local coproduction mechanism, the NUPDEC of Aracaju, through two articles and a technical-technological product. The first article structured, through an integrative review, the knowledge and experiences of Brazil and the world between the years 2019 to 2022, identifying elements that allowed the division and qualitative analysis into four categories: coproduction as a tool for social learning, local governance and adaptation, strategic knowledge management at the local scale and coproduction as a tool for climate democracy. The second article explored the strategies adopted by the NUPDEC of Aracaju/SE to train, motivate and engage its actors. Through the content analysis of the documents, connections were developed with the categories previously defined in the first article, revealing, according to the theoretical model, the consonance with nominal and symbolic coproduction. It was identified that improvements are needed in training and in the Aracaju Resilience Plan, in order to make NUPDEC effective as a local co-production mechanism in the prevention of climate risks, which are suggested in the Intervention Proposal.